Assessing Language Delay in Twins: Low Gesture Use and Birth History Factors. Issue 4 (October 2021) - Foran, Lori G.; Evans, Kelli J.; Beverly, Brenda L.
Abstract : Identification of language disorders in children younger than 3 years remains challenging despite agreement that early intervention improves outcomes. This study of twin language and gesture development substantiated the twinning effect, an unexplained lag in expressive and receptive language seen in twins, for a group of 88, 16- to 18-month-old twins who did not present with extreme perinatal risk. A valid, parent-report measure revealed word production of 10th percentile and less for 15 twins. Pregnancy complications, but not a positive family history of speech, language, or learning disorders or other case history factors, significantly increased the odds of this early expressive delay. The twinning effect was more pronounced for gesture than for spoken vocabulary: 29 twins fell below gesture norms. This was unexpected. Because gesture signals early communicative intentionality, twins with early expressive delay who present with limited gestures, with or without additional risk factors, warrant priority consideration for early intervention.